Investigating the salinity impacts on current and future water use and crop production in a semi-arid agricultural watershed - Hosseini Ghasemabadian, Pardis, author; Bailey, Ryan T., advisor; Arabi, Mazdak, committee member; Smith, Ryan, committee member; Andales, Allan, committee member (Colorado State University. Libraries, 2024)
Soil salinity can have a significant impact on agricultural productivity and crop yield, particularly in arid and semi-arid irrigated watersheds wherein irrigation and inadequate drainage often combine to increase salt ion concentrations in soil water. In conjunction with intense irrigation in semi-arid agricultural regions, increasing population resulting in boosted water demand, adverse impacts of climate change on water availability, in other words, water scarcity, future land use and land cover changes, changes in applied irrigation practices, and introducing new point-sources and non-point sources of salinity in the region all can govern the salinity and crop yield consequently. Taking into account the aforementioned impactful components on crop reduction via salinity increase, the overall objective of this dissertation is to provide insights for policymakers to better address the current and future salinity issues to sustain crop production in semi-arid regions under progressive salinity. This will be accomplished by i) investigating the controlling factors on salinity in the soil, groundwater, and river water using the SWAT-Salt model which simulates the reactive transport of 8 major salt ions in major hydrological pathways applied to a 1118 km2 irrigated stream-aquifer system located within the Lower Arkansas River Valley (LARV) in southeastern Colorado, USA ii) Assessing the salinity impacts on crops production blue and green water footprint as a measurable indicator for water being used per unit of a given crop production using the SWAT-MODFLOW-Salt model applied to a 732 km2 irrigated stream-aquifer system located in the LARV, iii) quantify the impact of environmental factors alteration including changes in climatic and irrigation practices in the LARV on future salinity content and its impact on crop production in the region using the SWAT-MODFLOW-Salt model. To control salinity, more importantly in semi-arid irrigated areas, the principal step is to identify the key environmental and hydrologic factors that govern the fate and transport of salts in these irrigated regions. To accomplish this objective, global sensitivity analysis was applied to the newly developed SWAT-Salt model (Bailey et al., 2019), which simulates the reactive transport of 8 major salt ions (SO4, Ca, Mg, Na, K, Cl, CO3, and HCO3) in major hydrologic pathways in a watershed system. The model was applied to a saline 1118 km2 irrigated stream-aquifer system located within the Lower Arkansas River Valley in southeastern Colorado, USA. Multiple parameters including plant growth factors, stream channel factors, evaporation factors, surface runoff factors, and the initial mass concentrations of salt minerals MgSO4, MgCO3, CaSO4, CaCO3, and NaCl in the soils and in the aquifer were investigated for control on salinity in groundwater, soils, and streams. The Morris screening method was used to identify the most sensitive factors, followed by the Sobol' variance-based method to provide a final ranking and to identify interactions between factors. Results showed that salt ion concentration in soils and groundwater was controlled principally by hydrologic factors (evaporation, groundwater discharge and up flux, and surface runoff factors) as well as the initial amounts of salt minerals in soils. Salt concentration in the Arkansas River was governed by similar factors, likely due to salt ion mass in the streams controlled by surface runoff and groundwater discharge from the aquifer. Sustainable agriculture in intensively irrigated watersheds, especially those in arid and semi-arid regions, requires improved management practices to sustain crop production. This depends on factors such as climate, water resources, soil conditions, irrigation methods, and crop types. Of these factors, soil salinity and climate change are significant challenges to agricultural productivity. To investigate the long-term impact of salinity and climate change on crop production from 1999 to 2100 in irrigated semi-arid regions, we applied the water footprint (WF) concept using the hydro-chemical watershed model SWAT-MODFLOW-Salt, driven by five General Circulation Models (GCMs) and two climate scenarios (RCP4.5 and RCP8.5), to a 732 km2 irrigated stream-aquifer system within the Lower Arkansas River Valley (LARV), Colorado, USA. In this study we estimated the green (WFgreen), blue (WFblue), and total (WFtotal) crop production WFs for 29 crops in the region, both with and without considering the impact of salinity on crop yield. The results indicate that during the baseline period (1999-2009), the total annual average WFgreen, WFblue, and WFtotal increased by 7.6%, 4.4%, and 6.5%, respectively, under salinity stress, with crop yields decreasing by up to 4.6%, 1.6%, and 2.3% for green, blue, and total crop yield. The combined impact of salinity and the worst-case climate model (IPSL_CM5A_MR) under the higher emission scenario (RCP8.5) resulted in increases of 3.3%, 1.9%, and 3% in green, blue, and total crop production WFs. Additionally, the study found that the proportion of green, blue, and total crop production WFs in the LARV exceeded the world average. This discrepancy was attributed to various factors, including different spatial and temporal crop distribution, irrigation practices, soil types, and climate conditions. Notably, salinity stress had a more significant impact on green crop yield and green WF compared to blue crop yield and blue WF across all GCM models. This finding highlights the need to prioritize management practices that address salinity-associated challenges in the region. The adverse effects of salinity on soil health, crop yield, and environmental ecosystem require comprehensive strategies for managing salinity in agricultural watersheds by adopting improved irrigation practices and effective salinity management strategies for mitigating these impacts and sustaining agricultural productivity in salinity-affected regions. The complex dynamics between various irrigation practices and soil salinity play a pivotal role in shaping agricultural productions and managing soil salinity. In semi-arid regions like the LARV, salinity poses a significant threat to agriculture, exacerbated by climate change and historic irrigation practices. To evaluate the interplay between salinity, climate change, and irrigation management in affecting crop yields within the Lower Arkansas River Valley (LARV), focusing on corn and alfalfa, we utilized the SWAT-MODFLOW-Salt model to examine how changes in irrigation management influence crop production under various scenarios projected through the year 2100. This study addresses the differential responses of corn and alfalfa to the impact of incremental increases and reductions in irrigation efficiency and irrigation water loss (5%, 10%, 15%, and 20%) on corn and alfalfa yields dynamics under salinity stress, utilizing projections from five global climate models under two distinct Representative Concentration Pathway (RCP) scenarios, RCP4.5 and RCP8.5 and two irrigation scenarios. The findings from irrigation practice scenario (1), maintaining a constant amount of irrigation water, revealed that corn yields improved by up to 13.8% under salinity stress and 16.5% under non-salinity conditions with a 20% increase in irrigation efficiency and a 20% reduction in water loss under RCP4.5. Alfalfa, demonstrating greater salinity tolerance, showed similar benefits, with yield increases of 9.1% under salinity stress and even higher improvements under non-salinity conditions. These results highlight the effectiveness of tailored irrigation practices in mitigating environmental stresses. In contrast, scenario (2), which involved reducing irrigation water by half, resulted in more pronounced negative outcomes. Corn yields exhibited greater sensitivity to salinity stress, with yield reductions ranging from -9.8% under salinity stress to -9.3% under non-salinity conditions, particularly under the RCP8.5 scenario. Alfalfa yields also declined, though less severely than corn, with reductions ranging from -8.9% under salinity stress to -8.3% under non-salinity conditions. Despite improvements in irrigation efficiency and reduced water loss, the adverse effects of salinity stress were not fully mitigated in scenario (2), emphasizing the need for adequate water availability to sustain crop yields under salinity and climate change pressures. The research highlights the importance of adopting advanced irrigation technologies and practices that not only counteract the adverse effects of salinity but also adapt to evolving climatic conditions. This study offers valuable insights for policymakers and agricultural managers on strategic water resource management to sustain crop yields in salinity-affected and water-limited agricultural systems. The results of this study can be used in decision-making regarding the most impactful land and water management strategies for controlling salinity transport and build-up in soils, both for this watershed and other similar semi-arid salinity-impacted watersheds for present and future purposes.
Keywords: hydrological modeling; SWAT-MODFLOW-Salt; water footprint; salinity; crop production; SWAT-Salt